2022
DOI: 10.1021/acsanm.2c03662
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Cytotoxicity of Nano Gallium Liquid Metal Droplets for Biomedical Applications

Abstract: Gallium-based liquid metals (LMs) have emerged as novel materials for biomedical applications. Gallium (Ga) is considered significantly less toxic than other LMs, such as mercury. However, Ga droplets have not been thoroughly assessed for their cytotoxicity. Here, we report the concentration-dependent cytotoxic effects of Ga nano- and microdroplets on HaCaT cells, a human keratinocyte cell line. We found that Ga droplets demonstrated substantial cytotoxic effects at 1000 μg/mL after 24 h exposure, while lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Altogether, this data indicates that the Ga droplets, while having a modest antibacterial effect, are not highly effective antibacterial agents in isolation refuting the current assumption in the field that Ga is a robust antimicrobial agent. The mechanism underpinning this modest effect may be through a combination of physical interactions or as more widely reported the release of Ga 3+ ions. , As mentioned previously, solutions containing 2 mg/mL of Ga droplets were found to contain 15 μg/mL of Ga 3+ after 24 h (Figure S5), which is similar to results of previous studies . This indicates that Ga 3+ concentrations above 15 μg/mL are required for substantial antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, this data indicates that the Ga droplets, while having a modest antibacterial effect, are not highly effective antibacterial agents in isolation refuting the current assumption in the field that Ga is a robust antimicrobial agent. The mechanism underpinning this modest effect may be through a combination of physical interactions or as more widely reported the release of Ga 3+ ions. , As mentioned previously, solutions containing 2 mg/mL of Ga droplets were found to contain 15 μg/mL of Ga 3+ after 24 h (Figure S5), which is similar to results of previous studies . This indicates that Ga 3+ concentrations above 15 μg/mL are required for substantial antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24]31 As mentioned previously, solutions containing 2 mg/mL of Ga droplets were found to contain 15 μg/mL of Ga 3+ after 24 h (Figure S5), which is similar to results of previous studies. 61 This indicates that Ga 3+ concentrations above 15 μg/mL are required for substantial antibacterial activity. The superior antibacterial activity reported in the literature may be due to the presence of trace heavy metals in the sources of the gallium used.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A recent study has investigated the concentration-dependent cytotoxic effects of Ga nano- and microdroplets on HaCaT cells, a human keratinocyte cell line . The researchers found that Ga droplets had substantial cytotoxic effects on these cells at 1000 μg/mL after 24 h of exposure, while at concentrations of 500 μg/mL, only a slight reduction in cell viability was recorded.…”
Section: Introductionmentioning
confidence: 99%
“…Since GaLMs can interact with both prokaryotic and eukaryotic cells, it is important to fully understand the interactions between GaLMs and mammalian cells. Although some human cell types have been studied, ,, the more fundamental understanding should be gained regarding the interactions between other cell types and GaLMs as well as subsequent outcomes. Such studies will provide further evidence, allowing for full evaluation of the potential of GaLMs as an antimicrobial agent.…”
Section: Introductionmentioning
confidence: 99%
“…Water splitting via a Ga–Al composite offers a nonpolluting route to nano-Al­(OH) 3 from postconsumer Al, in addition to producing economically and environmentally valuable H 2 fuel . The reaction also serves as a simple and quick method for the synthesis of Ga NPs, which, in addition to other liquid metal nanoparticles, have attracted attention in a wide variety of fields from biomedicine to catalysis. Additionally, the current literature lacks a comprehensive investigation into the production of aluminum hydroxide/oxyhydroxide through liquid metal water splitting reactions, particularly involving simple and efficient binary Ga–Al composites (Scheme ).…”
Section: Introductionmentioning
confidence: 99%